The Nordic difference: Job quality in Europe 1995–2010 - Oinas, Tomi; Anttila, Timo; Mustosmäki, Armi; Nätti, Juoko (Nordic Journal of Working Life Studies, 2012)
Previous empirical research has pointed out that Nordic countries are distinguished from the rest of Europe in terms of job quality. On the other hand, it has been debated whether, in the longer run, the Nordic welfare state is able to insulate workers from globalization effects. This article investigates whether Nordic countries have retained their advantageous position concerning job quality compared with other EU countries. Empirical analyses are based on the European Working Conditions Survey collected in 1995, 2000, 2005, and 2010. We use data on employees in the 15 member states of the EU prior to enlargement in 2004 (n = 61,457). The results partly confirm previous findings of high job quality in the Nordic countries. However, there are clear differences between Nordic countries. To be precise, Denmark stands out from the rest of Europe and other Nordic countries with its higher level of job quality.